2000
DOI: 10.1002/(sici)1097-0185(20000501)259:1<76::aid-ar9>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone wound healing after maxillary molar extraction in ovariectomized aged rats: Quantitative backscattered electron image analysis

Abstract: The processes of bone wound healing after maxillary molar extraction in ovariectomized aged rats were examined by means of quantitative backscattered electron image analysis and energy-dispersive X-ray microanalysis. Six-month-old female rats were either sham-operated or underwent bilateral ovariectomy (OVX), and 60 days postoperatively, the maxillary first molars were extracted. On post-extraction days 7, 30, and 60, the dissected and resin-embedded maxillae were micromilled in the transverse direction throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 39 publications
6
27
0
Order By: Relevance
“…In our previous BSE observations, newly-formed bone at this site was significantly decreased by ovariectomy (Shimizu et al, 2000). The mean area of newly-formed bone mass on the buccal side of extracted alveolar sockets at 60 days after molar extraction, however, was only 85.4 m 2 /1,000 m at 7 days post-ovariectomy [present data], whereas that at 60 days post-ovariectomy was 358.3 m 2 / 1,000 m (Shimizu et al, 2000).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In our previous BSE observations, newly-formed bone at this site was significantly decreased by ovariectomy (Shimizu et al, 2000). The mean area of newly-formed bone mass on the buccal side of extracted alveolar sockets at 60 days after molar extraction, however, was only 85.4 m 2 /1,000 m at 7 days post-ovariectomy [present data], whereas that at 60 days post-ovariectomy was 358.3 m 2 / 1,000 m (Shimizu et al, 2000).…”
Section: Discussionsupporting
confidence: 54%
“…In OVX rats, the newly-formed bone area (m 2 /1,000 m) was significantly (*P Ͻ 0.01) reduced as compared with that in sham-operated controls at 60 days after molar extraction. the buccal alveolar bone surfaces after molar extraction continues until the late phase post-ovariectomy (Shimizu et al, 1998(Shimizu et al, , 2000, post-menopausal estrogen deficiency is suggested to be a strong risk factor for poor bone wound healing and bone strength after tooth extraction. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these points, the bone-specific surface may be affected depending on structural changes. Therefore, if the bone parameters by micro-CT are associated with bone loss in osteoporosis, values of BMD, bone volume/tissue volume, trabecular thickness, and trabecular number will decrease, and trabecular separation and bone surface/bone volume will increase (21,22). In this study, trabecular thickness and low trabecular number were higher in the gHA group than in the pHA group.…”
Section: Discussionmentioning
confidence: 49%
“…Previous reports have indicated that as with other osteoporotic bones, there are negative effects on implant treatment in the socket of an extracted tooth, including a decrease in the rate of bone formation, alveolar bone interdental bone thickness, and in the density and thickness of the mandibular inferior cortex (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%